The Jakarta Heart Center’s (JHC) Communication Strategy for Improving Cardiovascular Health Literacy Among Young People - Sophia Bernadette; Sylvia A. Ronnfeld; Prilly Latuconsina (International Journal Labs, 2026)
This study aims to evaluate the communication strategies of Jakarta Heart Center (JHC) in enhancing heart health literacy among young adults, given the rising trend of cardiovascular diseases within the productive age group. The research employs a qualitative approach using a case study method. Data were collected through in-depth interviews with JHC management, observations of digital communication channels, and a review of relevant literature. The analysis is guided by Ronald D. Smith’s strategic communication planning model, which consists of four key stages: (1) Research, to identify communication problems and understand the target audience; (2) Strategy, to formulate communication objectives and determine appropriate approaches; (3) Tactics, involving the selection of media, messages, and communication activities; and (4) Evaluation, to assess the effectiveness of the communication program. Findings reveal that although JHC has utilized various social media platforms such as Instagram and TikTok, its communication strategies have not been fully effective in reaching younger audiences. This limitation is primarily due to the lack of interactive and visually educational content, as well as challenges in translating technical medical information into simple narratives that are easily understood by the general public. This study contributes to the development of more inclusive and adaptive health communication strategies tailored to the media consumption behavior of younger generations. By applying Ronald D. Smith’s framework, the research underscores the importance of comprehensive audience research, creative and interactive content development, and continuous evaluation to reduce the risk of heart disease from an early age.